Influence of Geographical Location on Maternal-Infant Microbiota: Study in Two Populations From Asia and Europe - Cheng, Yue; Selma-Royo, Marta; Cao, Xin; Calatayud, Marta; Qi, Qi; Zhou, Jing; Zeng, Lingxia; Garcia-Mantrana, Izaskun; Collado, Maria Carmen; Han, Bei (Frontiers in Cellular and Infection Microbiology, 2022)
Early gut microbial colonization is driven by many factors, including mode of birth, breastfeeding, and other environmental conditions. Characters of maternal-neonatal microbiota were analyzed from two distinct populations in similar latitude but different continents (Oriental Asia and Europe). A total number of 120 healthy families from China (n=60) and Spain (n=60) were included. Maternal and neonatal microbiota profiles were obtained at birth by 16S rRNA gene profiling. Clinical records were collected. Geographical location influenced maternal-neonatal microbiota. Indeed, neonatal and maternal cores composed by nine genera each one were found independently of location. Geographical location was the most important variable that impact the overall structure of maternal and neoantal microbiota. For neonates, delivery mode effect on neonatal microbial community could modulate how the other perinatal factors, as geographical location or maternal BMI, impact the neoantal initial seeding. Furthermore, lower maternal pre-pregnancy BMI was associated with higher abundance of Faecalibacterium in maternal microbiota and members from Lachnospiraceae family in both mothers and infants. At genus-level, Chinese maternal-neonate dyads possessed higher number of phylogenetic shared microbiota than that of Spanish dyads. Bifidobacterium and Escherichia/Shigella were the genera most shared between dyads in the two groups highlighting their importance in neonatal colonization and mother-infant transmission. Our data showed that early gut microbiota establishment and development is affected by interaction of complex variables, where environment would be a critical factor.